The Basic Principles of Training Future Teachers to Work With Younger Students With Experience of Traumatic Effects - Belousova, Alla; Grinko, Anna; Fedotova, Olga; Nusaiba, Marachli; Shiraz, Alali (International Journal of Cognitive Research in Science, Engineering and Education (IJCRSEE), 2021)
The article shows that the unstable situation in the world leads to possible armed conflicts, affecting primarily children, experiencing various traumatic consequences. Such a situation arises in post-conflict regions and creates a need for teachers who possess the necessary competencies when teaching children with experience of traumatic effects. The purpose of the article is to study the state and trends in the development of psychological and pedagogical issues related to the use of collaborative learning technologies to form the psychological culture of future teachers in order to further work with children with experience of traumatic effects. It is shown that the analysis of the formation and development of the problems of group psychological corrective work is grounded on the basic principles identified by representatives of various directions. The authors propose to build the training of future teachers on the basis of a model of joint thinking for the subsequent organization of teachers’ interaction with children who have experience of traumatic effects. The authors analyzed the basic principles of group psychologically corrective work from the point of view of the possibilities of organizing joint thinking. The basic principles of the organization of training of future teachers were highlighted, their meaningful characteristics for the purposes of organizing joint thinking were given. A comparison of the principles of group psychological corrective work and the principles of the organization of joint thinking of future teachers is carried out. Their correlation and the importance of using joint thinking in organizing the training of future teachers and for conducting psychologically corrective work with children are shown.